13C NMR spectroscopic characterization of organic material of soils from a neolithic settlement located in upper Bavaria - Bäumler, Rupert; et al. (2nd European Symposium "NMR in Soil Science", 2000)
UnivIS-Import:2015-04-16:Pub.2000.nat.dgeo.IG.zentr.13cnmr

A contribution to soil fertility assessment for arid and semi-arid lands - Hag Mohamed Husein, Hussam; Lucke, Bernhard; Bäumler, Rupert; Sahwan, Wahib (Soil Systems, 2021)
Soil fertility must be viewed as a dynamic concept that involves the constant cycling of nutrients between organic and inorganic forms. In this context, it refers also to supply adequate amounts of water and aeration for plant growth. Soil fertility under arid and semi-arid lands is constrained not only by limited water availability but also by small organic matter contents. Most fertility assessment systems are based on organic matter contents as the main parameter. However, crop experiments from various irrigated arid and semi-arid soils indicate that productivity is less-affected by organic matter contents than assumed. Therefore, we propose a new soil fertility system for dryland soils. It is a rule-based set of algorithms, mainly using additions and subtractions. Soil, climate, and landscape factors are integrated to calculate the numerical value of fertility for a given soil. We expect the system, which is focused on soil properties that keep or increase optimum soil moisture (such as texture), to be applicable in arid and semi-arid lands and to provide more realistic estimates of fertility regarding agricultural purposes. The manuscript will provide an outline of the main aspects of the system, illustrated by various case applications.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Ac-quired fertility; Inherent fertility; Nonagricultural land; Nutrients; Organic matter; Water retention

Agricultural suitability of dune system and Limpopo Basin soils near Xai-Xai, Mozambique - Bäumler, Rupert; Samimi, Cyrus; Brandt, Martin (South African Journal of Plant and Soil, 2009)
Quaternary dune systems, as well as the Limpopo Basin near the rural city of Xai-Xai in southern Mozambique were studied concerning their soil fertility and sustainability for crop cultivation. Due to population growth, most sites, which are not overbuilt, are used for crop production. The Arenosols and Regosols of the dune area have slope of 20° and sandy textures. A poor water-holding capacity and a low capability of bonding nutrients are the consequence. A lack of food prevents a disciplined crop rotation including longer fallow periods. Despite persistent cultivation for decades, the soils have a high base saturation, but already a slight decline in the base saturation has considerable effects on crop quality. Shifting cultivation along the coastal dunes leads to a massive clearing of woodlands which destabilises the sensitive dune systems and exposes them to erosion. The Fluvisols of the Limpopo River valley on the other hand cannot be used without restrictions either. High salt contents influence plant growth and the clayey soils constrain root penetration, water availability, drainage and cultivation. Nevertheless, the soils are rich in nutrients and organic matter, and there is no water stress, even during the dry season. The valley soils appear to be a reasonable platform for agriculture.
UnivIS-Import:2015-03-09:Pub.2008.nat.dgeo.IG.profes_1.agricu
Keywords: Arenosol; Dune soils; Fluvisol; South-East Africa; Tropical soils

An approach for the characterization of Neolithic soils by means of chemolytic techniques and 13C NMR spectroscopy - Bäumler, Rupert; et al. (Mitteilungen der Deutschen Bodenkundlichen Gesellschaft, 1999)
UnivIS-Import:2015-03-05:Pub.1999.nat.dgeo.IG.profes_1.anappr

Andic properties in soils developed from non-volcanic materials in Central Bhutan - Bäumler, Rupert; et al. (Journal of Plant Nutrition and Soil Science, 2005)
UnivIS-Import:2015-03-09:Pub.2005.nat.dgeo.IG.profes_1.andicp

Arsenic release and speciation in a degraded fen as affected by soil redox potential at varied moisture regime - Bäumler, Rupert; Weigand, Harald; Mansfeldt, Tim; Schneckenburger, D.; Wesselbothe, S.; Marb, C. (Geoderma, 2010)
Soil surveys have demonstrated arsenic (As) contents of up to 1600mgkg in surface horizons of degraded fens in the Bavarian Molasse basin, Germany. Ground water from the Tertiary aquifer seems to be the primary source of As. Yet, the cause of its accumulation in the topsoil is unclear. Focussing the influence of redox processes on As redistribution, we conducted soil column experiments with the A (716mg Askg), Ag (293mg Askg) and 2Ag (37mg Askg) horizons of a Mollic Gleysol (pH 7.2). The fixed beds were equipped with redox electrodes and suction cups and subjected to a saturation-drainage-saturation cycle. Water table fluctuations were simulated by defined pressure heads applied to the lower column boundaries via a digitally controlled vacuum system. After water saturation, the redox potential (E) dropped to minimum values of around 0mV in the A/Ag and-400mV in the 2Ag horizon. Soil drainage resulted in a quick return to oxidising conditions. Both in the A and Ag horizons total aqueous As concentrations were low (up to 20μgl) and not related to E. In contrast, aqueous As concentrations of the 2Ag horizon were between 5 and 140μgl and increased as the E decreased. However, the As species distribution showed no clear trend with E since both As(III) and As(V) were detected under reducing conditions. High release of As in the 2Ag horizon is consistent with low contents in Fe (hydr)oxides. In the A and Ag horizons, pedogenetic enrichment of sesquioxides contributes to a comparably lower sensitivity of E to water saturation and favours As retention. Thereby, As released under saturated conditions in the 2Ag horizon may be stabilised in the topsoil following capillary rise. Thus, surface horizons may act both as historic and as recent sinks for geogenic As at the site. © 2010 Elsevier B.V.
Keywords: Arsenic release; As (III); As (V); Column experiments; Gleysols; Soil-groundwater interactions

Atmospheric deposition and impact of forest thinning on the throughfall of mountain forest ecosystems in the Bavarian Alps - Bäumler, Rupert; et al. (Forest Ecology and Management, 1997)
The input into two forested watersheds in the Bavarian Alps is characterised by 2000 mm mean annual precipitation. Evaporation from the tree crown surfaces varies between 25 and 30%. The input is influenced by multiple natural and man-made processes. In addition to the general climate, these are local weather conditions, the growing season, processes of combustion (traffic and domestic fuel), tourism, farming, and not least by processes in the canopy. The input of SO4-S is comparatively low, while high amounts of acidity and nitrogen are deposited. The input occurs mainly as dissolved salts. A considerable amount of the acidity deposited is buffered in the canopy by cation exchange and by calcareous dusts, which are blown out from the limestone and dolomite mountains nearby, and redeposited on leaf surfaces. Forest thinning (removal of 40% of the stem volume) caused marked changes in the deposition pattern. Interception and deposition rates of individual ions were reduced by up to 45%. The amount and chemical composition of the throughfall occupied an intermediate position between bulk precipitation and the throughfall of the control watershed. Ions which are preferentially exchanged and leached from the leaves, e.g. potassium and organic compounds, were affected the most.
UnivIS-Import:2015-03-05:Pub.1997.nat.dgeo.IG.profes_1.atmosp
Keywords: Forest thinning; Mountain forests; Throughfall chemistry; Watershed

Bodenschutz - Bäumler, Rupert (Lehrbuch Geographie, 2006)
UnivIS-Import:2015-04-20:Pub.2006.nat.dgeo.IG.profes_1.bodens

Böden und Bodennutzung in Bhutan - Gratwanderung zwsichen Ressourcenschutz und Ernährungssicherung - Bäumler, Rupert (Geographische Rundschau, 2007)
UnivIS-Import:2015-03-09:Pub.2007.nat.dgeo.IG.profes_1.bdenun

Characteristics of Some Wild Olive Phenotypes (Oleaster) Selected from the Western Mountains of Syria - Hamid, Reem Abdul; Hag Mohamed Husein, Hussam; Bäumler, Rupert (Sustainability, 2022)
This study presents the evaluation of some technological and production specifications of 20 selected wild olive (oleaster) phenotypes from Hama Province, western–central Syria. The analyses of oil quantity showed that the olive oil (OO) extracted ranged from 10.43 to 29.3%. The fatty acid composition determined by gas chromatography (m/m%, methyl esters), conforming to commercial standards, showed the percentages of palmitic (ranged 13.2–15.06%), stearic (2.27–4.2%), arachidic (0.42–0.7%), palmitoleic (0.73–1.25%), oleic (64.29–73.17%), linoleic (8.96–16.45%), and linolenic (0.23–1.6%). Our results suggest that, despite being in a harsh environment and lacking agricultural service, two wild olive phenotypes (WA4, WA6) are interesting since their fruits showed high-quality properties (fruit weight 2.16, 3.24 g; flesh 75.83, 86.2, respectively), high content of OO% (29.27, 29.01, respectively), and better fatty acid composition (oleic % 68.45, 66.74, respectively). This enables them to be a very promising introductory feature in olive genetic improvement processes. Thus, both phenotypes were adopted tentatively as inputs, the first for oil purposes and the second for dual purposes (oil and table olives). It will be important to further evaluate these promising phenotypes in terms of their OO minor compounds, as well as their ability to resist biotic and abiotic stresses.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Accession; Biodiversity; Fatty acid composition; Genetic improvement; Oleaster; Oleic acid

Characterization of Andisols developed from nonvolcanic material in Eastern Nepal - Bäumler, Rupert; et al. (Soil Science, 1994)
Soils developed from mica schist in Eastern Nepal (The Himalayas) were investigated. All soil horizons were characterized by high organic carbon and extractable aluminum contents. Chemical and physical analyses indicated andic soil properties. No short-range order minerals could be detected. It is assumed that aluminum is linked to the organic matter, which leads to insolubilization and stabilization of the organic material against microbial degradation. The formation of Al-humus complexes instead of short-range order minerals is preferred if enough Al and water-soluble organic compounds are present. Al-humus complexes are considered responsible for the formation of Andisols from nonvolcanic parent material. The soil is classified as Dystric Haplustand, medial, mesic (US Soil Taxonomy). Copyright © 1994 by Williams & Wilkins.
UnivIS-Import:2015-03-05:Pub.1994.nat.dgeo.IG.profes_1.charac

Character, rates, and environmental significance of holocene dust accumulation in archaeological hilltop ruins in the southern levant - Lucke, Bernhard; Roskin, Joel; Vanselow, Kim; Bruins, Hendrik J.; Abu-Jaber, Nizar; Deckers, Katleen; Lindauer, Susanne; Porat, Naomi; Reimer, Paula J.; Bäumler, Rupert; Erickson-Gini, Tali; Kouki, Paula (Geosciences, 2019)
Loess accumulated in the Negev desert during the Pleistocene and primary and secondary loess remains cover large parts of the landscape. Holocene loess deposits are however absent. This could be due low accumulation rates, lack of preservation, and higher erosion rates in comparison to the Pleistocene. This study hypothesized that archaeological ruins preserve Holocene dust. We studied soils developed on archaeological hilltop ruins in the Negev and the Petra region and compared them with local soils, paleosols, geological outcrops, and current dust. Seven statistically modeled grain size end-members were identified and demonstrate that the ruin soils in both regions consist of mixtures of local and remote sediment sources that differ from dust compositions deposited during current storms. This discrepancy is attributed to fixation processes connected with sediment-fixing agents such as vegetation, biocrusts, and/or clast pavements associated with vesicular layers. Average dust accretion rates in the ruins are estimated to be 0.14 mm/a, suggesting that 30% of the current dust that can be trapped with dry marble dust collectors has been stored in the ruin soils. Deposition amounts and grain sizes do not significantly correlate with wind intensity. However, precipitation may have contributed to dust accretion. A snowstorm in the Petra region delivered a significantly higher amount of sediment than rain or dry deposition. Snowfall dust had a unique particle size distribution relatively similar to the ruin soils. Wet deposition and snow might catalyze dust deposition and enhance fixation by fostering vegetation and crust formation. More frequent snowfall during the Pleistocene may have been an important mechanism of primary loess deposition in the southern Levant.
CRIS-Team Scopus Importer:2019-05-17
Keywords: Aeolian dust; Archaeological sediment; Biocrusts; Clast pavements; Climate change; Holocene; Loess; Ruin soil; Snow; Vesicular layer

Chemical characterization of material from Neolithic pits in Southern Bavaria, Germany - Bäumler, Rupert; et al. (Int. Humic Substances Society Meeting, 2000)
UnivIS-Import:2015-04-16:Pub.2000.nat.dgeo.IG.zentr.chemic

Chemical composition of the organic matter in Neolithic soil material as revealed by CPMAS 13C NMR spectroscopy, polysaccharide analysis and CuO oxidation. - Bäumler, Rupert; et al. (Soil Science, 2001)
The archaeological site in Murr, Upper Bavaria, was settled throughout the entire Neolithic period, between 5500 and 2700 BC. Various pits and a ditch found in the area are distinct from the surrounding loamy soil because of the dark brown color of their filling materials. Although several artifacts have been discovered, at the present stage of research neither the nature of the filling material nor the function of pits and the ditch are well understood. Thus, the organic matter composition of 30 filling layers from 11 Neolithic pits found in this settlement was investigated and compared with that of a nearby Luvisol profile and two A horizons from contemporary Phaeozems. All samples were subjected to C and N analysis, soil lightness measurements, solid-state 13C CPMAS nuclear magnetic resonance (NMR) spectroscopy, and polysaccharide and lignin analysis. The organic carbon contents are higher in the Neolithic samples than in the Luvisol horizons, but they are generally lower than in the A horizons of contemporary phaeozemic soils developed from loess. The Neolithic samples have a much higher intensity in darkness than do the surrounding Luvisol horizons. The organic carbon content of the Neolithic samples correlates with the lightness value. Solid-state 13C NMR measurements revealed that this correlation is primarily because of their aromatic C content, which is considerably higher in the Neolithic samples than in the contemporary soils. Small polysaccharide amounts and no lignin-derived phenols were found in the Neolithic samples. Thus, the organic material filling the Neolithic pits is significantly different in overall chemical composition from the surrounding soil. It represents a highly altered, highly aromatic material showing no evidence of lignin degradation products and probably deriving from non-soil origins.
UnivIS-Import:2015-03-09:Pub.2001.nat.dgeo.IG.profes_1.chemic
Keywords: Filling matrix; Lignin degradation products; Neolithic pits; Polysaccharide amounts; Soil color; Soil lightness measurements; Solid-state

Composition of Modern Dust and Holocene Aeolian Sediments in Archaeological Structures of the Southern Levant - Lucke, Bernhard; Sandler, Amir; Vanselow, Kim; Bruins, Hendrik J.; Abu-Jaber, Nizar; Bäumler, Rupert; Porat, Naomi; Kouki, Paula (Atmosphere, 2019)
Archaeological structures are often filled with sediments and may serve as effective dust traps. The physical parameters and chemical composition of archaeological soils in hilltop ruins, ancient runoff-collecting terraces, and cleanout spoils of cisterns were determined in the Petra region in southern Jordan and the Northern Negev in Israel. Different types of ruins are characterized by certain soil structures, but could not be distinguished with regard to substrate composition. This reflects a predominance of aeolian processes for primary sedimentation, while fluvial processes seem to only re-distribute aeolian material. In the Petra region, the physical and chemical properties of all archaeological soils show a significant local contribution from associated weathered rocks. Compared to modern settled dust, archaeological soils in Southern Jordan are enriched with various major and trace elements associated with clays and oxide coatings of fine silt particles. This seems connected with preferential fixation of silt and clay by surface crusts, and a role of moisture in sedimentation processes as calcareous silt was found to be deposited in greater amounts when associated with precipitation. In contrast, the contribution of rocks is negligible in the Negev due to greater rock hardness and abundant biological crusts that seal surfaces. Archaeological soils in the Negev are chemically similar to current settled dust, which consists of complex mixtures of local and remote sources, including significant portions of recycled material from paleosols. Archaeological soils are archives of Holocene dust sources and aeolian sedimentation processes, with accretion rates exceeding those of Pleistocene hilltop loess in the Negev. Comparison with Pleistocene paleosols suggests that dust sources did not change significantly, but disappearance of snow could have reduced dust accumulation during the Holocene.
CRIS-Team WoS Importer:2020-01-31

Ecozones and soils – An introduction - Bäumler, Rupert (Encyclopedia of Soils in the Environment, 2023)
The pedosphere and biosphere together, despite their marked differences, form the skin of the Earth's terrestrial ecosystems. The ecozonal concept is one of the first concepts to enable classification of both soils and the biosphere. Climatic factors are the main trigger that creates the differences within soils or soil types, within ecosystem sub-types, and between both. This chapter provides a short introduction to the chapters with a special focus on soils and soil types that follow a zonal concept, but also on soils which follow the law of exception, both are within the Pedology Section of the second edition of the Encyclopedia of Soils in the Environment.<br
Keywords: Ecozonal concept; Pedosphere; Soils and ecosystem; Zonal-azonal-intrazonal soils

Effect of forest management on the soil solution of mountain forests in the Bavarian Alps - Bäumler, Rupert (Vila Reall, Book of Abstracts, 2000)
UnivIS-Import:2015-04-16:Pub.2000.nat.dgeo.IG.zentr.effect

Effects of forest thinning on the streamwater chemistry of two forest watersheds in the Bavarian Alps - Bäumler, Rupert; et al. (Forest Ecology and Management, 1999)
Two well-buffered mountain forest watersheds were studied with regard to streamwater chemistry and the impact of forest thinning. The areas are located in the Bavarian Alps near lake Tegernsee, 50 km southwest of Munich. In order to get information about the influence of disturbances on the streamwater chemistry 40% of the trees were removed from one watershed after two years of monitoring. The trees were removed by crane to avoid soil damage and erosion. The second watershed was used as a reference. The output at the weirs is characterized, in general, by a strong export of silicate, alkali and alkaline earth cations, and bicarbonate. Acidity and nitrogen accumulate in the watersheds. Both areas are subject to a continuously increasing load of acidity. The acidity is mainly buffered by cation exchange and silicate hydrolysis. This is indicated by continuously decreasing pH values and the dominance of Ca2+ and silicic acid in the streamwater. Strong changes in the water chemistry along the flowpath indicate that rainwater will be stored in the system for sometime, and water derived from the headwater areas influences the discharge. During precipitation events the new rainwater replaces pre-event water, stored in soils, which had a longer contact time with the biotic and abiotic soil matrix. Acute effects of the selective harvest are leveled in the streamwater by multiple buffer reactions. The discharge of the disturbed watershed was increased by the reduction of interception and transpiration. Increased rates of mineralization and acidity loads caused an increase in ion concentration and solution load in the discharge from the disturbed area. NH4/+ showed the strongest effects compared to the reference area and the pre-event period. The changes in the runoff returned to pre-event conditions about one year after the disturbance.
UnivIS-Import:2015-03-05:Pub.1999.nat.dgeo.IG.profes_1.effect
Keywords: Acidification; Forest thinning; Mountain forests; Selective harvest; Streamwater chemistry; Watershed

Ernährungszustand gutwüchsiger Fichten und Tannen eines Bergmischwaldes im Flysch (Tegernseer Alpen) - Bäumler, Rupert; et al. (Forstwirtschaftliches Centralblatt, 1995)
UnivIS-Import:2015-03-05:Pub.1995.nat.dgeo.IG.profes_1.ernhru

Evidence for isovolumetric replacement in some terra rossa profiles of Northern Jordan - Bäumler, Rupert; Lucke, Bernhard; Kemnitz, Helga (Boletín de la Sociedad Geológica Mexicana, 2012)
We investigated the rock-soil transition zones of three different Terra Rossa profiles near the ancient site of Abila, in northern Jordan, in order to demonstrate the possibility of a metasomatic origin for these soils using a scanning electron microscope (SEM) equipped with an energy-dispersive system (EDS). The field interpretation suggested that the first Terra Rossa might partially have formed by isovolumetric replacement, the second appeared to represent mainly the residue of the underlying limestone, and the third seemed to be derived from colluvial material. However, all investigated rock-soil transition zones showed microfossils that had partially been replaced by clay, which could be geochemically confirmed using EDS. The replacement matrix was free of detrital clay and revealed a jelly-like, amorphous structure. Large phyllosilicates, some rare feldspars, and heavy minerals that occurred throughout the investigated rock-soil transition zones are probably remains of sandy interlayers in the weathered limestone. We conclude that isovolumetric replacement contributes to Terra Rossa formation in northern Jordan although it is not yet possible to quantify the extent of its contribution or the sources that supply the elements triggering the pressure-driven growth of clay minerals.
Keywords: Isovolumetric replacement; Metasomatism; Micromorphology; Rock-soil transition; Terra rossa

Evidence of middle Pleistocene glaciation in SW-Kamtchatka - Bäumler, Rupert; et al. (Zeitschrift für Gletscherkunde und Glazialgeologie, 1997)
UnivIS-Import:2015-03-05:Pub.1997.nat.dgeo.IG.profes_1.eviden

Fine silt and clay mineralogical changes of a soil chronosequence in the Langtang valley (Central Nepal) - Bäumler, Rupert; Zech, Wolfgang; Madhikermi, Dhruba P. (Journal of Plant Nutrition and Soil Science, 1997)
Chemical and raineralogical properties of a soil chronosequence in the high mountain zone between 3857 m and 4120 m a.s.l. in Central Nepal (Langtang valley) are presented. The soils have been developed in moraine deposits which consist of acid gneisses. They were classified as Entisols, and Spodosols. XRD analyses of the clay and fine silt fraction show increasing changes with distance from the recent Lirung glacier, depending on the time of deposition, resp. soil age. Alteration of illite to interstratified minerals and to hydroxy-Al interlayered minerals or pedogenic chlorite with increasing soil development could be observed. The interstratified minerals could be identified as random and regular illite-interlayered vermiculite mixed-layer minerals. Intensification of the X-ray signals of the fine silt fraction is given compared to the clay. With increasing soil development differences between the clay and fine silt fraction seem to increase. Indications are given of interstratification of the mica-pedogenic chlorite and chlorite-interlayered vermiculite type in the more intensively weathered soils. © VCH Verlagsgesellschaft mbH, 1997.
UnivIS-Import:2015-03-05:Pub.1997.nat.dgeo.IG.profes_1.finesi

Geochemical investigation of soils developed in different lithologies in Bhutan, Eastern Himalayas - Bäumler, Rupert; et al. (Geoderma, 2006)
Within a project studying soil genesis on the southern slopes of the Eastern Himalayas, a comprehensive set of major, trace and rare earth element (REE) contents has been compiled for the first time. Six saprolites and their associated pedons were sampled on metamorphic, migmatitic and leucogranitic parent materials at altitudes ranging from 1520 m to 3770 m. Metamorphic soils are largely illitic, with Si decreasing, and Al and Fe increasing with decreasing degree of metamorphism. The subsoil of a tourmaline-bearing leucogranite is characterised by equally high Si, but higher contents of K and lower Fe, Mg and Ti. A migmatitic profile in southern Bhutan is dominated by hornblende, and is quite distinct from the other lithologies with lower contents of Si and K, but higher Fe, Mg, Ca and Mn. Chondrite-normalised REE patterns compare with post-Archaean materials, with steep light rare earth (LREE) and flat heavy rare earth (HREE) patterns. In comparison to generalised upper crustal composition (UCC), the Bhutanese lithologies show a pronounced Eu anomaly. Whereas the patterns appear rather homogenised in topsoils, the influence of the parent materials causes deviations from the general trend with increasing depth. The occurrence of marine Tethyan sediments is confirmed by a strong positive Ce anomaly in the Central Bhutanese Phobjikha Valley. In the leucogranitic profile, REE depletion is attributed to the presence of monazite, as corroborated by trace element behaviour. Because of the hornblende, REE patterns of the migmatitic profile are flat and without a Eu anomaly. Chemical indices of alteration (CIA) of between 71 and 92 indicate advanced weathering, even at high altitudes. Correlation analyses show that REE are associated with the silt and clay fraction (< 63 μm). At elevations above approximately 3500 m, physical weathering causes passive REE enrichment, however no differentiation of REE concentrations or patterns within the profile is observed. Below 3500 m, increased chemical weathering and leaching appears to be sufficient to release and translocate REEs. In this process, HREE are preferentially translocated, whereas Ce is more refractory than the other lanthanides. This case study confirms that soil weathering and REE behaviour are closely related. © 2006 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2006.nat.dgeo.IG.profes_1.geoche
Keywords: CIA; Rare earth elements; Soil genesis; Tethyan sediments; Weathering

Grassland soils in the cool–arid–temperate ecozone (Steppe, grassland) - You, Mengyang; Xiaobing, Liu; Bäumler, Rupert; Oliver, Margaret A (Encyclopedia of Soils in the Environment (Second Edition)., 2023)
Most Mollisols–Chernozems are recognized as inherently productive and fertile soils that have formed under prairie–steppe grassland ecosystems. Their characteristics result from their formation under grassland and a cool–arid–temperate climate in the continental interiors of the northern and southern hemispheres. The effective moisture, mineral weathering, clay translocation, and secondary carbonates are the main factors that determine the environment of pedogenesis in prairie–steppe grassland regions. The distinctive characteristics of Mollisols–Chernozems are a black or dark topsoil with a large organic matter content. They have experienced major land-use change from natural grassland to intensive agriculture, which has led to a decrease in soil organic carbon (SOC) content; they are the breadbaskets of the world.<br
Keywords: Chernozems; Classification; Distribution; Kastanozems; Loess; Mollisols; Phaeozems; Soil organic carbon

Heterotrophic microbial communities use ancient carbon following glacial retreat - Bäumler, Rupert; et al. (Biology Letters, 2007)
When glaciers retreat they expose barren substrates that become colonized by organisms, beginning the process of primary succession. Recent studies reveal that heterotrophic microbial communities occur in newly exposed glacial substrates before autotrophic succession begins. This raises questions about how heterotrophic microbial communities function in the absence of carbon inputs from autotrophs. We measured patterns of soil organic matter development and changes in microbial community composition and carbon use along a 150-year chronosequence of a retreating glacier in the Austrian Alps. We found that soil microbial communities of recently deglaciated terrain differed markedly from those of later successional stages, being of lower biomass and higher abundance of bacteria relative to fungi. Moreover, we found that these initial microbial communities used ancient and recalcitrant carbon as an energy source, along with modern carbon. Only after more than 50 years of organic matter accumulation did the soil microbial community change to one supported primarily by modern carbon, most likely from recent plant production. Our findings suggest the existence of an initial stage of heterotrophic microbial community development that precedes autotrophic community assembly and is sustained, in part, by ancient carbon. © 2007 The Royal Society.
UnivIS-Import:2015-03-09:Pub.2007.nat.dgeo.IG.profes_1.hetero
Keywords: Carbon; Chronosequence; Microbial communities; Organic matter

Holocene dust dynamics archives in archaeological ruins in arid and semi-arid environments in the Southern Levant - Lucke, Bernhard; Bäumler, Rupert (Arabian Journal of Geosciences, 2021)
Ruins of archaeological structures, mainly dating to the Bronze Age till Byzantine period, were investigated in a case study in the Petra region in southern Jordan and in the northern Negev desert in Israel. They are covered by post-abandonment debris sediments which provided the parent material of initial soils now developed on the ruins. Such debris sediments have so far rarely been studied although they likely contain a significant aeolian dust fraction because structures and wall remains may act as effective dust traps. We analyzed different types of archaeological structures: cult sites on hilltops, runoff-irrigated terraces on slopes, and cisterns including associated cleanout mounds. As well, we collected current aeolian sediments in nearby dry marble dust traps. It was expected that the various ruins and location types would matter for sediment properties, but substrate composition in all investigated structures was similar. This suggests that most of the fine fractions of the debris material were primarily supplied by wind whereas fluvial processes only re-distributed aeolian sediments. A major aeolian contribution from local weathered rocks could be observed in the Petra region, but not in the Negev, which seems connected with the geology. In situ pedogenesis in both investigation regions is negligible. The ruins seem to act as current dust collectors, but their sediments cannot directly be compared with the material collected in nearby dry marble dust traps. Analogies to different types of collectors for aeolian sediments can be made: depending on design, dust traps gather aeolian material differently. Standard dry marble dust collectors are characterized by similar size of settling dust samples as compared to average aeolian deposition in the ruins, but are of dissimilar substrate composition with regard to particle size distribution and contents of major and trace elements. Sediments in the archaeological structures in southern Jordan show finer textures and higher contents of most major and trace elements which may indicate preferential fixation of silt and clay against sand in the ruins, whereas sediments in dry marble dust collectors in Jordan are relatively depleted in silt and clay. This could be due to crusts and clast covers because the studied archaeological hilltop structures were found covered by surface crusts and pavements of stones and pottery sherds. These may mirror the effect of desert pavements. In addition, current dust samples suggest that precipitation during aeolian sedimentation, in particular in case of snow, is connected with enhanced deposition of (possibly clay-coated) silt. Sediments in the archaeological structures include material from remote and local sources as well as from "recycled" paleosols. Average hilltop dust accretion rates were calculated as similar to 0.14 mm/year, which is in good agreement with results from dry marble dust collectors. They exceed rates calculated for Pleistocene hilltop loess in the Negev. This seems due to enhanced dust fixation in the archaeological ruins as compared to natural Negev loess soils, underlining a so far rarely considered but important role of sediment fixation mechanisms.
CRIS-Team WoS Importer:2021-12-10

Humifizierungsstatus und Stabilität der organischen Substanz im Deponiekörper - Bäumler, Rupert; et al. (Statusbericht Bayerischer Forschungsverbund Abfallforschung und Reststoffverwertung BayFORREST, 2000)
UnivIS-Import:2015-04-16:Pub.2000.nat.dgeo.IG.zentr.humifi

Impact of forest interventions on the water regime and water quality of mountain ecosystems in the Bavarian Alps - Bäumler, Rupert; et al. (Écologie, 1998)
UnivIS-Import:2015-03-05:Pub.1998.nat.dgeo.IG.profes_1.impact

Integrative Hochgebirgsökologie in der Hochschullehre – “Umweltwandel in den Südalpen” - Peters, Thorsten; Bäumler, Rupert; Bräuning, Achim; Grießinger, Jussi; Richter, Michael (Arbeitskreis Hochgebirge, 2013)

Investigations on the intensity of weathering of soils developed from glacial and fluvioglacial deposits and their relationship with the history of the landscape in the Mt. Everest region - Bäumler, Rupert; et al. (Geoderma, 1991)
Soils developed from glacial and fluvioglacial deposits in the Mt. Everest region (Eastern Nepal) were differentiated analytically with regard to weathering intensity and age. Iron fractionation, clay mineral analysis and the calculation of weathering indices resulted in a separation of the soils into two groups. One group, of "young soils' with their main weathering zone in the top horizons, has developed from deposits of the last ice age or postglacial events; this was supported by radiocarbon dating. The other group, of considerably older, highly weathered soils, was presumably derived from interglacial deposits. Based on these results and according to the soil geographical evidence, indications on the Pleistocene history of the landscape and the extent of the last major glaciation could be deduced. © 1991.
UnivIS-Import:2015-03-05:Pub.1991.nat.dgeo.IG.profes_1.invest

Investigations on the intensity of weathering of soils developed from glacial and fluvioglacial deposits and their relation to the glacial history of Central and Eastern Nepal - Bäumler, Rupert; et al. (European Bulletin of Himalayan Research (EBHR), 1993)
UnivIS-Import:2015-03-05:Pub.1993.nat.dgeo.IG.profes_1.invest

Microbial reduction of Fe(III) and turnover of acetate in Hawaiian soils. - Bäumler, Rupert; et al. (Fems Microbiology Ecology, 2002)
Soils contain anoxic microzones, and acetate is an intermediate during the turnover of soil organic carbon. Due to negligible methanogenic activities in well-drained soils, acetate accumulates under experimentally imposed short-term anoxic conditions. In contrast to forest, agricultural, and prairie soils, grassland soils from Hawaii rapidly consumed rather than formed acetate when incubated under anoxic conditions. Thus, alternative electron acceptors that might be linked to the anaerobic oxidation of soil organic carbon in Hawaiian soils were assessed. Under anoxic conditions, high amounts of Fe(II) were formed by Hawaiian soils as soon as soils were depleted of nitrate. Rates of Fe(II) formation for different soils ranged from 0.01 to 0.31 μmol (g dry weight soil)-1 h-1, but were not positively correlated to increasing amounts of poorly crystallized iron oxides. In general, sulfate-reducing and methanogenic activities were negligible. Supplemental acetate was rapidly oxidized to CO2 via the sequential reduction of nitrate and Fe(III) in grassland soil (obtained near Kaena State Park). Supplemental H2 stimulated the formation of Fe(II), but H2-utilizing acetogens appeared to also be involved in the consumption of H2. Approximately 270 μmol Fe(III) (g dry weight soil)-1 was available for Fe(III)-reducing bacteria, and acetate became a stable end product when Fe(III) was depleted in long-term incubations. Most-probable-number estimates of H2- and acetate-utilizing Fe(III) reducers and of H2-utilizing acetogens were similar. These results indicate that (i) the microbial reduction of Fe(III) is an important electron-accepting process for the anaerobic oxidation of organic matter in Fe(III)-rich Hawaiian soils of volcanic origin, and (ii) acetate, formed by the combined activity of fermentative and acetogenic bacteria, is an important trophic link in anoxic microsites of these soils. © 2002 Federation of European Microbiological Societies. Published by Elsevier Science B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2002.nat.dgeo.IG.profes_1.microb
Keywords: Acetate; Acetogenesis; Fe(III) reduction; Volcanic soil

Natural abundance radiocarbon in soil microbial biomass: Results from a glacial foreland - Bäumler, Rupert; Garnett, Mark H.; Bol, Roland; Bardgett, Richard D.; Wanek, Wolfgang; Richter, Andreas (Soil Biology & Biochemistry, 2011)
We present a method for determining the natural abundance radiocarbon (C) content of soil microbial biomass (SMB) based on existing fumigation-extraction procedures. We applied the technique to soils from the foreland of the Ödenwinkelkees glacier in the Austrian Alps, which has a well-characterised chronosequence of soils at different stages of development. Across the chronosequence, SMB contained post-bomb levels of C, suggesting it was substantially composed of carbon that had been fixed since the 1960s. Comparison of our results with previous findings from the same site showed that at most stages in the sequence the SMB had a similar C content to the bulk soil organic matter (SOM). However, soil respired CO was C-depleted relative to SMB, indicating that at least a component of the microbial community was mineralising some older carbon. In the most recently exposed soils, SMB was C-enriched compared to both soil respiration and SOM, suggesting that a small component of the microbial biomass that utilises older carbon contributes disproportionately more to the CO efflux. Although other interpretations are possible, this explanation is consistent with the notion that early on in the succession a large proportion of the microbial biomass is dormant. © 2011 Elsevier Ltd.
Keywords: Carbon; Glacial foreland; Microbial biomass; Radiocarbon

Overview chapter on factors of soil formation - Bäumler, Rupert; Oliver, Margaret A; Stockmann, Uta (Encyclopedia of Soils in the Environment, 2023)
Dokuchaev first introduced formally the concept of factors of soil formation, which act and interact at different spatial and temporal scales. This chapter provides an overview of these factors, which is followed by chapters on most of the specific factors. Climate has a major effect on soil formation because it affects the weathering of rocks and the mineral soil, and vegetation and organisms, which play a major role in changing rocks and sediments to soil. Parent material underpins soil particle-size distribution, chemistry and physics. Relief affects soil hydrology and human use of the soil. Finally, human influence on soil formation has now been recognized as a factor.<br
Keywords: Biota; Climate; Human activities; Parent material; Relief; Soil forming factors; Time

Palaeoenvironments during MIS 3 and MIS 2 inferred from lacustrine intercalations in the loess-palaeosol sequence at Bobingen (southern Germany) - Mayr, Christoph; Matzke-Karasz, Renate; Stojakowits, Philipp; Lowick, Sally; Zolitschka, Bernd; Heigl, Tanja; Mollath, Richard; Theuerkauf, Marian; Weckend, Marc-Oliver; Bäumler, Rupert; Gregor, Hans-Joachim (E&G : Quaternary Science Journal, 2017)

Pedochemical characterisation and landscape history of the Thangbi river terrace system, central Bhutan. - Bäumler, Rupert; Caspari, Thomas; Baillie, Ian; Tshering, Kado; Dorji, Tshering; Norbu, Chencho (Zeitschrift für Geomorphologie, 2004)
The properties and development of soils formed on fluvial deposits in the valley of the river Chamkhar Chhu, 10 km north of Jakhar, central Bhutan, were examined. Fieldwork in 2000 and 2002 revealed a system of at least 28 river terraces rising to relative heights of nearly 300 meters. The largest and still well preserved terrace of the system is of late Pleistocene age. Polygenetic structures & buried topsoils indicate several interruptions of soil development under periglacial conditions. 14C AMS dating suggests discontinuities at approximately 10,175, 8,710, 4,055 and 1,715 years BP. Pedochemical analyses showed that all examined soils are moderately weathered and leached and can mostly be classified as Cambisols. X-ray diffraction analyses of clay fractions revealed that especially on the upper terraces pedogenic chlorite formed at the expense of illite. Weighted profile averages of texture, specific surface area (BET), pedogenic iron compounds and weathering indices show significant trends within the terrace system and indicate that weathering and soil development continuously become more intense with increasing relative height above the current river level. © 2004 Gebrüder Borntraeger, D-14129 Berlin · D-70176 Stuttgart.
UnivIS-Import:2015-03-09:Pub.2004.nat.dgeo.IG.profes_1.pedoch

Pedogenesis in eolian deposits in the high mountain area of Eastern Nepal. - Bäumler, Rupert (Quaternary international, 2001)
UnivIS-Import:2015-03-09:Pub.2001.nat.dgeo.IG.profes_1.pedoge

Pedogenic studies in eastern Nepal new aspects about the last glaciation. - Bäumler, Rupert (Quaternary Science Reviews, 2004)
Soil development of high mountain soils was studied in eastern Nepal with regard to new aspects about the Quaternary history of landscape and climate. The soils were developed in Quaternary glacial deposits, i.e. the lowest clearly identified terminal and lateral moraines of 5 high valleys of the Khumbu and Solu region, all located between 3800 and 4300masl. Particle size analysis, pedogenic iron oxides and weathering indices were used to obtain information on soil development of the different sites. Except for one site no significant differences were found in the extent of soil development indicating that all soils and their corresponding glacial deposits are of similar relative age. In combination with recently published numerical datings of the terminal moraines in one of the high valleys, the age of the deposits could be narrowed down partly correcting former findings. The maximum extent of the last glaciation, if accepted as more or less synchronous to the global Last Glacial Maximum, was less pronounced than previously assumed. However, morphological and pedological findings give evidence of an early phase of Late Pleistocene glaciation further down valley corresponding to new results from High Asia, the Japanese Alps, North Siberia, and the Kamchatka peninsula. © 2004 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2004.nat.dgeo.IG.profes_1.pedoge

Pedogeochemical studies and palaeoenvironmental implications in Kichik Alay Mountain soils (Kyrgyzstan) - Bäumler, Rupert; et al. (Zeitschrift für Geomorphologie, 2003)
UnivIS-Import:2015-03-09:Pub.2002.nat.dgeo.IG.profes_1.pedoge

Pedogeochemical studies and palaeoenvironmental implications in southern Kamchatka (Russia) - Bäumler, Rupert (-, 2001)
UnivIS-Import:2015-04-16:Pub.2001.nat.dgeo.IG.profes_1.pedoge_5

Pedology—Basic principles - Bäumler, Rupert; Stockmann, Uta; Oliver, Margaret A (Encyclopedia of Soils in the Environment, 2023)
This chapter encompasses the basic principles of pedology, the study of soils in their natural setting. It provides basic information about the formation and properties of soils from any kind of parent material, the factors that influence soil formation at the Earth's surface, the induced processes, and the role of soils in the environment.<br
Keywords: Pedogenesis; Soil formation; Soil properties; Transformation processes; Translocation processes

Physisch-Geographisches Geländepraktikum - Bräuning, Achim; Bäumler, Rupert; Feick, Sebastian; Grießinger, Jussi (FAU Erlangen-Nürnberg, Institut für Geographie, 2012)
Keywords: Geografiestudium; Physische Geografie; Raumbeobachtung

Quaternary Paleosols, Tephra Deposits and Landscape History in South Kamchatka, Russia - Bäumler, Rupert; et al. (Catena, 2000)
Paleosols developed in various glacial and glaciofluvial deposits of potentially different ages in the southern Kamchatka peninsula of Russia are covered by multiple layers of volcanic ash and have been affected by permafrost. Weathering indices and iron fractionation data indicate slight differences in soil development between the paleosols on terminal moraines and associated terraces of two different ages in the central part of the region, suggesting that the two depositional phases were separated by an interstadial rather than an interglacial. According to the extent of weathering and the age of the oldest tephra overlying the paleosols (ca. 8000 BP), both sets of deposits are of Late Pleistocene age. Glacial deposits on the west coast of the peninsula differ from those on the east in containing ice-wedge casts. Also, the paleosol here is less developed and is covered by lake sediments as well as tephra units. The oldest tephra, dated to ca. 40,000 BP, is present only in the west, suggesting that the western glacial deposits date from an older (Middle Pleistocene?) glaciation. (C) 2000 Elsevier Science B.V.
UnivIS-Import:2015-03-06:Pub.2000.nat.dgeo.IG.profes_1.quater
Keywords: Glacial deposits; Iron oxides; Paleosols; Tephra; Weathering indices

Questioning Transjordan's historic desertification: A critical review of the paradigm of 'empty lands' - Lucke, Bernhard; Shunnaq, Mohammed; Walker, Bethany; Shiyab, Atef; Al-Muheisen, Zeidoun; Al-Sababha, Hussein; Bäumler, Rupert; Schmidt, Michael (Levant, 2012)
European travel reports of the 19th century and excavations in Transjordan created the impression that population numbers were strongly reduced during the Islamic periods, leading to 'empty' lands which were only resettled during the early 20th century. This development was considered to be caused by bad (Muslim) governance, nomadic incursions, and environmental degradation. However, our case study near the ancient site Abila of the Decapolis in northern Jordan found that the land was never empty and always fertile, but there is evidence for a rapid and intense landscape change during the Late Byzantine period. This was probably caused by a significant shift to aridity which also triggered socio-economic changes in subsistence strategies from agriculture to nomadism. The climatic change seems to have occurred rapidly within approximately 100 years in the late 6th and early 7th centuries AD and was accompanied by heavy rainfall events. It might have been caused or triggered by the climatic event of the 'Mystery Veil' which the Byzantine historian Procopius described in the year 536 AD. During the Medieval period, settlement density increased again until another decline took place in the late Ottoman period. However, the vicinity of Abila was probably never abandoned and the continuity of place names speaks against a larger exchange of population. Rising population numbers and favourable climatic conditions in the early 20th century caused most tribes to settle again, which improved government control. © Council for British Research in the Levant 2012.
Keywords: Abandonment; Abila of the decapolis; Climate change; Land degradation; Mystery Veil; Overgrazing

Red mediterranean soils in jordan: New insights in their origin, genesis, and role as environmental archives - Lucke, Bernhard; Kemnitz, Helga; Bäumler, Rupert; Schmidt, Michael (Catena, 2014)
It is disputed whether Terrae Rossae form mainly out of the bedrock residue, from allochthonous material like aerosols, or by isovolumetric replacement. Furthermore, whether they are mainly relic soils or are still forming is subject to debate. These questions were addressed by comparing the geochemistry of several limestone and basalt based Red Mediterranean Soils with Lithosols on sandstone and limestone in Jordan. The bedrock residue was included at all test sites. Paleosols and initial soils on the limestone Regolith of historic ruins delivered insights into the possible time frame of soil development. A major reduction of elements in the soils compared to bedrock could be observed for CaO in carbonaceous, SiO in arenaceous, and FeO and MgO in basaltic rocks. All Terrae Rossae, however, are characterised by a significant increase of SiO, AlO, TiO, FeO, KO, and a range of mainly metallic minor elements that cannot be derived from the bedrock. A reasonable explanation could be input via aeolian transfer of minerals, with clay minerals as the major carrier plus quartz. This input probably originates in Egypt and Sudan and has remained largely unchanged over long periods. Growing aridity during the Holocene has apparently increased the share of silt while clay deposition and soil development has been reduced. At some sites, metasomatic processes have contributed to soil development and might help to explain the depth of some profiles. However, formation of red soils during the Holocene seems very limited, and the Red Mediterranean Soils may represent remains of a paleolandscape. © 2013 Elsevier B.V.
Keywords: Aeolian deposition; Isovolumetric replacement; Paleosol; Red Mediterranean Soil; Residue; Terra Rossa

Regolith and soils in Bhutan, Eastern Himalayas. - Bäumler, Rupert; et al. (European Journal of Soil Science, 2004)
Bhutan lies at altitudes of 100-7500 m on the steep, long and complex southern slopes of the Eastern Himalayas. Soil surveys show that, despite steep gradients, there are many moderately or deeply weathered soils. Many slopes are mantled with polycyclic, layered drift materials, so soil horizons owe as much to regolith heterogeneity as to pedogenesis. In the limited arable areas soil profiles are further complicated by rice cultivation and the construction, maintenance and irrigation of flat terraces on steep slopes. Some natural pedogenic horizonation is apparent, and there is an altitudinal zonation of soil types. Although the climate is warm and seasonally wet, most soils on the subtropical southern foothills are not particularly weathered and leached. The foothills are seismically active, and many soils are formed in unstable landslide debris. Elsewhere the regoliths are more stable. The main soils up to about 3000 m in the inner valleys are moderately weathered and leached, and have bright subsoil colours and thin dark topsoils. Above these there is a zone of bright orange-coloured non-volcanic andosolic soils. Further upslope there are acid soils with thick surface litter, stagnogleyic topsoils, and drab brown subsoils with organic cutans. These grade to weak podzols, which extend from about 3500 m up to the treeline, around 4000 m. Above this, alpine turf soils, with deep, dark, and friable topsoils and yellowish friable subsoils, are intermixed with unweathered glacial deposits. The interactions between pedogenesis and the deposition of the varied and layered drift materials complicate mapping and classification of the soils.
UnivIS-Import:2015-03-09:Pub.2004.nat.dgeo.IG.profes_1.regoli

Relationships between spectral features, iron oxides and colours of surface soils in northern Jordan - Sahwan, Wahib; Lucke, Bernhard; Sprafke, Tobias; Vanselow, Kim; Bäumler, Rupert (European Journal of Soil Science, 2020)
Ground data on spectral characteristics of Jordan's soils remain sparse, which makes the interpretation of remote sensing datasets challenging. These are, however, very useful for predicting soil properties and agricultural suitability. Previous studies have shown that soil colours correlate well with degrees of weathering intensity, as indicated by magnetic parameters and dithionite-extractable iron (Fed) contents along a climosequence in northern Jordan. This study enlarges the database by the results of 160 bulk samples that were collected systematically from the soil surface at 40 locations. In addition to soil colour and contents of Fed, we explore mean soil reflectance spectra (MSRS) measured by analytical spectral devices (ASD) and analyse the morphological conditions of the spectra referring to the effects of iron oxides on spectral behaviours. Results show a high correlation of spectral behaviours and colour variations with Fe oxides, and no correlation with soil organic carbon Corg. The influence of the Fe oxide contents is clearly apparent in the visible range (VIS). The presence of CaCO3 increases the reflectance in all spectral ranges. Six soil groups (Gr. I - Gr. VI) were discerned qualitatively and quantitatively in the study area, which largely mirror the intensity of red colour expressed by redness indices. Highlights: In northwestern Jordan there is an evident connection between the spectral properties, chemistry and soil colour. This study established a preliminary spectral library of soils in NW Jordan to facilitate the use of remote sensing in soil studies. The morphological properties and statistical analysis of the spectral data show that spectra of soils in NW Jordan are dominated by iron oxides. Spectral properties can be used to characterize the soil colours and types of Fe oxides in soils of Jordan.
CRIS-Team Scopus Importer:2020-06-23
Keywords: ASD laboratory soil spectroscopy; CIELAB colour system; iron oxides; Mediterranean soils; soil colour

Relevance of soils for Gross National Hapiness. Wisdom, GNH, and Destiny of Nations. Seminar on Gross National Happiness - Bäumler, Rupert; et al. (Journal of Bhutan Studies, 2004)
UnivIS-Import:2015-03-09:Pub.2004.nat.dgeo.IG.profes_1.releva_6

Small scale distribution of Al, heavy metals, and PAH in an aggregated alpine podzol - Bäumler, Rupert; et al. (Geoderma, 1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dgeo.IG.profes_1.smalls

Soil development and paleoenvironment at the northwestern spur of High Asia - approach and implications - Bäumler, Rupert; et al. (-, 2000)
UnivIS-Import:2015-04-16:Pub.2000.nat.dgeo.IG.zentr.soilde

Soil development as an indicator of the Pleistocene and Holocene landscape history in Western Tienshan and Nepal. - Bäumler, Rupert; et al. (Marburger Geographische Schriften, 2000)
UnivIS-Import:2015-03-09:Pub.2000.nat.dgeo.IG.zentr.soilde_3

Soil development on Late Quaternary river terraces in a high montane valley in Bhutan, Eastern Himalayas - Bäumler, Rupert; Dorji, Tshering; Caspari, Thomas; Veldkamp, A.; Jongmans, A.; Tshering, Kado; Dorji, Tsheten; Baillie, Ian (Catena, 2009)
We examined the geochemistry and micromorphology of the soils on a suite of morphologically well-defined and visually distinct fluvial terraces, up to 40 m elevation above the current riverbed, at Thangbi in the upper Bumthang Valley, Bhutan. The alluvia forming each of the terraces are lithologically and structurally similar, with shallow or moderately deep, clast-free sandy loam overbank deposits capping deep clast-supported beds of rounded boulders and interstitial sand. The topsoils on the 40 m terrace have more silt than those on the lower terraces. The soils are interpreted mainly as a monoclinal post-incisive chronosequence. Features that indicate progressive pedogenesis with increasing elevation include subsoil rubefaction, crystallinity of free Fe sesquioxides, and weathering of susceptible primary minerals, such as biotite and hornblende. However other soil attributes show no systematic trends and the overall impression is of limited pedogenesis, even in the soils on the higher terraces. We examine possibilities that the immaturity of the soils is due to pedogenic rejuvenation by post-incision additions to the soil parent materials. © 2009 Elsevier B.V. All rights reserved.
Keywords: Chemical weathering; Cyclothem; Loess; Micromorphology; Pedogenesis; Soil chronosequence

Soil formation in Phobjikha Valley, Central Bhutan with special regard to the redistribution of loessic sediments. - Bäumler, Rupert; Caspari, Thomas; Norbu, Chencho; Tshering, Kado; Baillie, Ian (Journal of Asian Earth Sciences, 2009)
Soil development and landscape evolution were studied in the basin-shaped Phobjikha Valley at 2900-3200 m a.s.l., to the west of the Black Mountain Range, West Central Bhutan. The local environmental setting with strong along-valley winds, frequent freeze-thaw cycles, extensive dry periods and sparse vegetation cover seems to encourage the generation and short-distance transport of silt-sized particles. The effects of this process are evidenced in the smooth valley morphology and in the nature of the examined pedons. Their involvement in continuing redistribution of local sediments is reflected by a homogeneous silty-clayey and stone-free texture, varying profile depths, buried topsoils and weakly developed recent A horizons. In protected locations, in situ weathering of metamorphic parent materials results in alu-andic features with bulk densities <0.9 g cm-3, (Alo + 1/2Feo) > 2%, and phosphate retention >95%. Dominance by Al-hydroxy interlayered clay minerals and large amounts of well-crystallised iron oxides indicate an advanced stage of weathering. In areas of preferred eolian deposition, argic and ferralic features emerge, with clay contents of up to 60% and surface areas of >50 m2 g-1. Under forest, umbric horizons can develop. CECeff is below 10 cmolc kg-1 at all sites. Cluster and factor analyses of soil chemical and physical parameters confirm the redistribution of local sediments as a dominant factor behind the measured variables. No clear indication of glacial activities in the area was found, whereas the massive silty sediments in the lower parts of most profiles, the presence of debris slopes, and the asymmetric cross sections of the side valleys suggest periglacial conditions. Buried topsoils dated at about 2000 conventional 14C years BP indicate a weakening or absence of sediment influx under wetter conditions towards the end of the Holocene climate optimum. Charcoal on top of paleosols suggests that human activities of deforestation, grazing and arable agriculture may have contributed to the reactivation of local sediment redistribution until today. © 2008 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2009.nat.dgeo.IG.profes_1.soilfo
Keywords: Cumulic soils; Himalayas; Loess cycle; Non-volcanic Andosols; Paleoclimatology

Soil geographical and pedogeochemical studies on Pleistocene and Holocene glaciation in the northwestern Tien Shan (Uzbekistan) - Bäumler, Rupert; et al. (Zeitschrift für Gletscherkunde und Glazialgeologie, 1999)
UnivIS-Import:2015-03-05:Pub.1999.nat.dgeo.IG.profes_1.soilge_7

Soils and Land Use in the Decapolis Region (Northern Jordan). Implications for Landscape Development and the Impact of Climate Change - Bäumler, Rupert; Lucke, Bernhard; al-Saad, Ziad; Schmidt, Michael; Lorenz, S.-O.; Udluft, P.; Heußner, K.-U.; Walker, Bethany (Zeitschrift des Deutschen Palastina-Vereins, 2008)
UnivIS-Import:2015-03-09:Pub.2008.nat.dgeo.IG.profes_1.soilsa

Soils and Paleosols at Ba'ja - Bäumler, Rupert; et al. (Neo-lithics, 2007)
UnivIS-Import:2015-03-09:Pub.2007.nat.dgeo.IG.profes_1.soilsa

Soils in arid and semiarid regions: The past as key for the future - Lucke, Bernhard; Bäumler, Rupert; Nikolskii, I. (Springer Netherlands, 2013)
Growing populations, increasing food demand, and technological advances may soon lead to intensifying land use in semiarid and arid countries through the spread of irrigated agriculture. Improved water harvesting and desalinization technology, coupled with higher efficiency of regenerative energies, might allow to widely extend irrigated areas. While this is a positive development in the light of growing demands for water and food, it presents challenges for land-use planners. Negative examples like Lake Aral make clear that a careful analysis is required before embarking on large-scale irrigation projects. Soils are central for assessing the impacts of irrigation in the desert. For longterm projects as outlined above, it is insufficient to consider only the present soil distribution. It should also be considered how soils will change under irrigation. In this context, the past is a key for the future, since the modeling of future soil development can be calibrated using reconstructions. Soil surveys which consider the archival role of soils and sediments can partly be used to understand the landscape history and identify risk areas. Paleosols can be evaluated as indicators how changes of moisture availability will affect soil properties and which time frames are involved. This can be coupled with modeling of future soil development. A major methodological challenge for this approach is the use of different parameters and time frames in reconstruction and modeling, which have to be “translated” using experimentally determined relationships. Long-term, large-scale irrigation in arid regions will mean a significant change of the environment and a departure from the conservative idea of sustainability, toward a concept which has been named “progressive development.“ Its success chances depend largely on our understanding and correct prediction of the consequences of man-made changes of the environment.
Keywords: Arid and semi-arid; Dry land; Fertility index; Paleosols; Sustainable development

Soils of the high mountain region of Eastern Nepal: classification, distribution and soil forming processes - Bäumler, Rupert; et al. (Catena, 1994)
Eleven soil profiles of the Mt. Everest region (Dudh Kosi and Beni Khola valley) between 2,700 and 4,900 m a.s.l. were investigated to provide information about soil classification, zonal distribution, and changes in the chemical and mineralogical properties with elevation and climatic conditions. The soils are mainly developed from deposits of the last main glaciation which are predominated by paragneisses. They were classified as Entisols, Inceptisols, and Spodosols according to the U.S. Soil Taxonomy (Soil Survey Staff, 1990). Detailed chemical and clay mineralogical analyses indicate a strong influence of the elevation, integrating several factors of climatic conditions and bioclimatic zones, on soil types and soil forming processes. Inceptisols predominate in the hill zone and lower tropical mountain zone between 2,000 and 3,000 m a.s.l. They are replaced by Spodosols in the subalpine forest and alpine shrub zone up to 4,500 m. On eroded sites and locations above 4,500 m shallow and stony soils, classified as Entisols, are present. A linear decrease in the intensity of weathering with increasing elevation is shown by the decreasing clay content of the main weathering horizon. © 1994.
UnivIS-Import:2015-03-05:Pub.1994.nat.dgeo.IG.profes_1.soilso

Soil solution chemistry and impact of forest thinning in mountain forests in the Bavarian Alps - Bäumler, Rupert; et al. (Forest Ecology and Management, 1998)
The soil solution of two forested catchments in the Bavarian Alps was studied over a period of not quite four years with regard to the dynamics of solutes and the impact of forest thinning on the solution chemistry. Soil solution was obtained by porcelain tension cups from three depths (10, 30 and 50 cm). It is characterized by high concentrations of alkali and alkaline earth cations, and of silicate and bicarbonate. Solution chemistry in topsoil is influenced by atmospheric input, but the deposited acidity is almost completely and rapidly buffered through cation exchange and silicate weathering. The solution chemistry is further controlled by biogenetic processes including the release of ions by mineralization, and the temporary fixation of ions by biological immobilization and root uptake. Gaseous losses of N may occur due to a dominance of hydromorphic soils. Thinning (removal of 40% of the trees by thinning) caused strong changes of the solution chemistry. Except for silicate and sulfate the concentrations of all cations and anions increased mainly due to increased mineralization and the reduction of nutrient uptake by roots. Ammonium and nitrate showed the strongest effects. Solution chemistry returned to pre-event conditions one year after thinning due to the high buffer capacity of the soils.
UnivIS-Import:2015-03-05:Pub.1998.nat.dgeo.IG.profes_1.soilso
Keywords: Buffering processes; Forest thinning; Mineralization; Mountain forests; Soil solution

Soils on glacial and glaciofluvial deposits in Central and Eastern Nepal in relation to classification and landscape history - Bäumler, Rupert; et al. (Proceedings of the International Conference on Ecohydorlogy of High Mountain Areas, 1998)
UnivIS-Import:2015-04-16:Pub.1998.nat.dgeo.IG.profes_1.soilso_8

Soil texture and altitude, respectively, largely determine the floristic gradient of the most diverse fog oasis in the Peruvian desert - Münchow, Jannes; Hauenstein, Simon; Bräuning, Achim; Bäumler, Rupert; Rodriguez, Eric Frank; Von Wehrden, Henrik (Journal of Tropical Ecology, 2013)
Studying species turnover along gradients is a key topic in tropical ecology. Crucial drivers, among others, are fog deposition and soil properties. In northern Peru, a fog-dependent vegetation formation develops on mountains along the hyper-arid coast. Despite their uniqueness, these fog oases are largely uninvestigated. This study addresses the influence of environmental factors on the vegetation of these unique fog oases. Accordingly, vegetation and soil properties were recorded on 66 4 × 4-m plots along an altitudinal gradient ranging from 200 to 950 m asl. Ordination and modelling techniques were used to study altitudinal vegetation belts and floristic composition. Four vegetation belts were identified: a low-elevation Tillandsia belt, a herbaceous belt, a bromeliad belt showing highest species richness and an uppermost succulent belt. Different altitudinal levels might reflect water availability, which is highest below the temperature inversion at around 700 m asl. Altitude alone explained 96% of the floristic composition. Soil texture and salinity accounted for 88%. This is in contrast with more humid tropical ecosystems where soil nutrients appear to be more important. Concluding, this study advances the understanding of tropical gradients in fog-dependent and ENSO-affected ecosystems. © Cambridge University Press 2013.
Keywords: altitudinal zonation; diversity gradient; dry tropics; edaphic gradient; ENSO; floristic modelling; La Niña; South America; spatial analysis; species richness

Soil weathering on glacial and glaciofluvial deposits in the Langtang valley (Central Nepal) and its relation to the glacial history - Bäumler, Rupert; et al. (Zeitschrift für Geomorphologie, Supplementband, 1996)
Investigations of soil genesis on glacial and glaciofluvial deposits near Kyangjin in the Langtang valley, Central Nepal, and radiocarbon analysis were carried out to quantify the intensity of soil development and to date Holocene events. Iron fractionation and weathering indices resulted in a differentiation of the soils into groups of different soil development. The first group of very young soils are developed from deposits of the Little Ice Age. They had their main zone of weathering in the top horizons. The second group of soils, mainly Inceptisols and Spodosols, indicated advances of the Lirung glacier into the valley of Langtang Khola, which took place between 3100 and 500 years B.P. At about 6000 and 4400 yr B.P. climatic fluctuations occurred characterized by accelerated solifluction and deposition of eolian material following warmer periods with humus accumulation and soil formation. The relative-age estimates were supported by radiocarbon analysis.
UnivIS-Import:2015-03-05:Pub.1996.nat.dgeo.IG.profes_1.soilwe

Spectral Characteristics of Soil Types in Northwestern Jordan Considering Iron Oxides Effects and Colors - Sahwan, Wahib; Lucke, Bernhard; Sprafke, Tobias; Vanselow, Kim; Bäumler, Rupert (Springer Nature, 2022)
Remote sensing as a tool to map and monitor soil cover in Jordan is very significant for agriculture production. Nonetheless, the still poor state of information about spectral characteristics of Jordan's soils is a challenge, where the understanding of soil spectra is of essential importance. It is especially suited to demonstrate relationships between spectral reflectance data and various soil properties, which correspond to well-known relationships of color, mineral assemblages, and chemical compositions. This study explores the spectral characteristics of soil types in northern Jordan with regard to soil colors and explains the effects of iron oxides on the shape of the spectral curves. A total of 160 bulk samples were collected systematically from the soil surface at 40 locations. Based on laboratory measurements with analytical spectral devices (ASDs), a mean soil reflectance spectrum (MSRS) was calculated. Color measurements of soils were conducted with a spectrophotometer using the CIELAB color space (Commission Internationale de l'Eclairage CIE, (1978)). The results show high correlations between spectral characteristics, soil color variations, and Fe oxides. Whereas organic matter contents seem to play no detectable role. Based on these findings, we were able to distinguish six soil groups in the study area.
CRIS-Team Scopus Importer:2022-02-04
Keywords: Iron oxides; Jordan; Soil color; Soil spectra; Spectroscopy

Stabilization of inorganic contaminants on lead crystal polishing sludge. - Bäumler, Rupert; Weigand, Harald; Gretzbach, Tina; Marb, C. (2008)
Neutralization sludge from the lead crystal polishing process has a high leaching potential for a series of inorganic contaminants. Cost-effective treatment options would be desirable both for soil contaminated by this residue and for waste from current manufacturing. The feasibility of contaminant stabilization was studied in batch experiments using five phosphatic amendments. All additives reduced lead concentrations relative to the control presumably by formation of sparingly soluble lead phosphates. Arsenic and zinc concentrations were above the control in some treatments due to either competitive displacement or additive-borne secondary contamination. Both stabilization and mobilization were dose-dependent. Equilibration velocities were contaminant-specific and varied between treatments. Slowest kinetics and lowest stabilization efficiencies were observed for fluoride. Treatment optimization should therefore focus on combined amendments which address both lead and fluoride. Copyright ASCE 2008.
UnivIS-Import:2015-07-08:Pub.2008.nat.dgeo.IG.profes_1.stabil

Stoffeintrag und Stoffdynamik zweier Kleineinzugsgebiete im Flysch (Tegernseer Alpen) - Bäumler, Rupert; et al. (GSF-Bericht 39/93, 1993)
UnivIS-Import:2015-04-16:Pub.1993.nat.dgeo.IG.profes_1.stoffe

Streamwater chemistry in mountain forest watersheds of the Bavarian Alps Effects of forest use or natural disturbances. - Bäumler, Rupert (Geographica Helvetica, 2002)
UnivIS-Import:2015-03-09:Pub.2002.nat.dgeo.IG.profes_1.stream

The Decapolis region (Northern Jordan) as historical example of desertification? Evicence from soil development and distribution - Bäumler, Rupert; et al. (Quaternary international, 2006)
UnivIS-Import:2015-03-09:Pub.2006.nat.dgeo.IG.profes_1.thedec

Transformation of soil organic matter in Tussock grassland of New Zealand by Hieracium pilosella - Bäumler, Rupert; et al. (Biology and Fertility of Soils, 2000)
UnivIS-Import:2015-03-06:Pub.2000.nat.dgeo.IG.profes_1.transf

Untersuchungen zur Ernährung und Düngung von Weihnachtsbaum- und Schmuckreisigbeständen in einem Praxisbetrieb - Bäumler, Rupert; et al. (Allgemeine Forstzeitschrift für Waldwirtschaft und Umweltvorsorge, 1994)
UnivIS-Import:2015-03-05:Pub.1994.nat.dgeo.IG.profes_1.unters

Untersuchungen zur Stoffdynamik zweier bewaldeter Kleineinzugsgebiete im Flysch - Auswirkungen eines geregelten forstlichen Eingriffs - Bäumler, Rupert; et al. (Forstwirtschaftliches Centralblatt, 1995)
UnivIS-Import:2015-03-05:Pub.1995.nat.dgeo.IG.profes_1.unters

Volcanic soils and non-volcanic andic soils - Bäumler, Rupert; Uehara, G (Encyclopedia of Soils in the Environment, 2023)
The chapter informs about the formation and the variety of soils from volcanic parent materials, their pathways of weathering, their processes of soil formation, and their most important properties. A special focus is given on the classification of soils of the Andosol/Andisol type developed from non-volcanic parent materials, as their formation is not yet fully understood.<br
Keywords: Alu-andic; Andic properties; Andisols; Andosols; Ferro-andic; Human interactions; Non-volcanic Andosols; Non-allophanic; Spodic properties; Volcanic soils

Weathering of soils developed in the eolian material overlying glacial deposits in Eastern Nepal - Bäumler, Rupert; et al. (Soil Science, 1998)
We used the ratio between well crystallized Fe-oxides and total Fe (Fe(d-o)/Fe(t)) and weathering indices to study eight soils developed in eolian material overlying glacial deposits in Eastern Nepal with regard to intensity of soil development. Together with selected radiocarbon analyses and information on soil morphology, we tried to interpret the data in terms of relative and absolute age distinctions of the deposits. The results suggest no clear relationship between weathering intensity and morphostratigraphical development and the age of the geomorphic surface. We assume that this is attributable to different orographic conditions for sedimentation of the eolian dust at the study sites and to different degrees of pre-weathering of the eolian covers. However, we can show that formation of organic matter and soil development, in general, started around 2500-2800 years B.P. in the eolian cover of most soils studied. This indicates deposition of the bulk eolian sediments around 2800 years B.P. and earlier. Two soils have greater relative ages in the subsoil with respect to the weathering indices. In these soils, parts of the eolian sediments are of late glacial origin or even older. Distinct variation of soil development and weathering indices within a vertical distance of 200 m provided evidence of marginal ice.
UnivIS-Import:2015-03-05:Pub.1998.nat.dgeo.IG.profes_1.weathe
Keywords: Eolian sediments; Fe/Al fractionation; Nepal; Quaternary landscape; Soil weathering

Zur pleistozänen und holozänen Landschaftsgeschichte des Modi Khola-Tals (Annapurna, Nepal). - Bäumler, Rupert; et al. (Zeitschrift für Gletscherkunde und Glazialgeologie, 2001)
UnivIS-Import:2015-03-09:Pub.2001.nat.dgeo.IG.profes_1.zurple

Zur Problematik der pleistozänen und holozänen Vergletscherung Süd-Kamtschatkas - erste Ergebnisse bodengeographischer Untersuchungen - Bäumler, Rupert; et al. (E&G : Quaternary Science Journal, 1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dgeo.IG.profes_1.zurpro